Analisis Penafsiran Wahbah Az-Zuhaili terhadap Ayat-Ayat tentang Ghibah dalam Tafsir Al-Munir - Thahirrah, Al Athiyyah; Amril, Dapit (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2024)
The phenomenon of backbiting for society is a common thing to do so that someone does not think about the impact that occurs after doing backbiting.  The urgency of this research is to analyze Wahbah az-Zuhaili's interpretation of the verses about backbiting. As well as understanding the law of backbiting, the impact of backbiting and how to prevent it through this interpretation of Wahbah az-Zuhaili. This research was conducted qualitatively using the library method. Meanwhile, to analyze the interpretation of the ghibah verses by Wahbah az-Zuhaili, the character-based Maudu'I interpretation method, through content analysis, and the bil ma'tsur interpretation approach were used.  The results of this research show that Wahbah az-Zuhaili's interpretation regarding backbiting is also obtained, that there are 6 things that backbiting can be done according to the prevailing situation. Wahbah az-Zuhaili emphasized that this exception must be used with great care, so that it is not misused. This is the difference between Wahbah az-Zuhaili's interpretation and other commentators in interpreting the ghibah verse. In Wahbah az-Zuhaili's view backbiting can cause various impacts, such as damage to relationships, mental and physical difficulties, decline, and moral damage as well as being tortured in hell. In order to overcome acts of backbiting, always remember that backbiting is a very heinous act that is prohibited by Allah because it can have an impact on individuals and society.